Laser–RF synchronization based on digital phase detector - Yang, Jin; Du, Ying-Chao; Yan, Li-Xin; Huang, Gang; Du, Qiang; Xu, Yi-Lun; Huang, Wen-Hui; Chen, Huai-Bi (Nuclear science and techniques, 2017)
Laser oscillator synchronization with RF reference signal is ultra-important for a modern light source based on the accelerator. For Tsinghua Thomson scattering X-ray source, we have synchronized the mode-locked laser oscillator to RF reference signal with 48.2 fs RMS relative jitter. Both fundamental and harmonic signals derived from photo diode detection are used for laser-RF synchronization in our scheme. The fundamental signal is for coarse laser-RF synchronization and multiple laser oscillator synchronization. The harmonic signal is for high precise phase locking. The digital phase detector is implemented in the synchronization scheme for less noise, replacing the mixing to DC phase detection scheme. The digital processing algorithm for synchronization is commonly used in low-level RF control field. In order to test the phase locking loop logic without damaging the real laser oscillator,a laser oscillator emulator was developed for phase locking. This paper will report the laser-RF synchronization scheme and its performance. The laser oscillator emulator system will also be introduced here.